1996
DOI: 10.1021/ic9510728
|View full text |Cite
|
Sign up to set email alerts
|

One- vs Two-Electron Reduction of N2O Promoted by a Divalent Chromium Macrocyclic Complex

Abstract: Reaction of [Cr(ORPG)Li2(THF)4] (1) [ORPG = octaalkylporphyrinogen R = Et (a), n-Pr (b)] with N2O gave two different products depending on the solvent employed. While a deoxygenation reaction was observed in toluene with formation of the Cr(IV) complex [(THF)(ORPG)Cr(O)(LiTHF)2] (2), reactions carried out in THF yielded a Cr(III) species [Cr(ORPG)(THF)2][Li(THF)4] (3) where only one electron was transferred to N2O. The structures of 1b, 2a, and 3a have been elucidated by X-ray crystal structures. Crystal data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Interestingly, the chloride ligand trans to the NHC ligand, Cl(2), shows no sign of a significant trans influence exerted by the strongly σ-donating NHC ligand with the Cr(1)−Cl(2) bond length being intermediate in length of the three metal−chloride bonds. The THF ligand coordinated to the Cr in 3 has a bond length of 2.163(3) Å, which is in the range of other THF-coordinated complexes of Cr(III) . Complex 3 exhibits a room-temperature effective magnetic moment of 4.0(1) μ B , consistent with a d 3 ion having three unpaired electrons ( S = 3/2).…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, the chloride ligand trans to the NHC ligand, Cl(2), shows no sign of a significant trans influence exerted by the strongly σ-donating NHC ligand with the Cr(1)−Cl(2) bond length being intermediate in length of the three metal−chloride bonds. The THF ligand coordinated to the Cr in 3 has a bond length of 2.163(3) Å, which is in the range of other THF-coordinated complexes of Cr(III) . Complex 3 exhibits a room-temperature effective magnetic moment of 4.0(1) μ B , consistent with a d 3 ion having three unpaired electrons ( S = 3/2).…”
Section: Resultsmentioning
confidence: 93%
“…[20][21][22][23][24] For example, the stoichiometric reaction of N 2 O with a divalent Cr(II) porphyrinogen complex results in an oxo-Cr(IV) product. 20 In our system, reduction of an O-bound adduct would result in an Fe III -OH species and N 2 . Alternatively, an interaction may occur between Fe I and the central nitrogen of N 2 O. Semiempirical calculations on N 2 O have shown that the LUMO is largely localized on the central nitrogen atom, with the HOMO localized on the terminal oxygen and nitrogen atoms.…”
Section: Discussionmentioning
confidence: 99%
“…[6] N 2 Owould be an attractive alternative but has been considered to be rather unreactive and ap oor ligand [7a] although the formation of metal oxo species has been established. [7] In rare cases, cleavage of the NÀNb ond occurs. [8] Thei nsertion of the oxygen atom of N 2 Oi nto am etal-carbon [9] or am etalhydride bond, [10] yielding alkoxy,a ryloxy,o rh ydroxy com-plexes,h as been reported.…”
mentioning
confidence: 99%